The establishment of the fertile fish lineages derived from distant hybridization by overcoming the reproductive barriers. Issue 6 (June 2020) - Liu, Qingfeng; Liu, Junmei; Yuan, Liujiao; Li, Lu; Tao, Min; Zhang, Chun; Qin, Qinbo; Chen, Bo; Ma, Ming; Tang, Chenchen; Liu, Shaojun
Abstract : Distant hybridization refers to the cross between two different species or higher-ranking taxa. It is very significant if the new lineages with genetic variation, fertile ability, and improved characteristics can be established through distant hybridization. However, reproductive barriers are key limitations that must be overcome to establish fertile lineages derived from distant hybridization. In the present review, we discussed how distant hybridization is an important way to form new species by overcoming reproductive barriers and summarized effective measures to overcome reproductive barriers in order to create fertile lineages of fish distant hybridization. In addition, we described the utilization of the fish lineages derived from distant hybridization. Finally, we discussed the relationship between distant hybridization and Mendel's laws, which generally apply to the inbred hybridization. We aim to provide a comprehensive reference for the establishment of fertile fish lineages by overcoming reproductive barriers and to emphasize the significance of fish distant hybridization in the fields of evolutionary biology, reproductive biology, and genetic breeding.